PENGARUH KOMBINASI PEMBERIAN PUPUK KOMPOS DAN PENGATURAN JARAK TANAM TERHADAP PERTUMBUHAN, KOMPONEN HASIL DAN HASIL TANAMAN JAGUNG (Zea mays L.) VARIETAS PIONEER 21 - Hendrayana, Hendrayana; Tadjudin, Endang; Nur, Subandi (Agroswagati : Jurnal Agronomi, 2022)
This experiment aims to determine the effect of Combination of Compost Fertilizer and plant spacing on Growth, Yield and Yield Components of Corn (Zea mays L.) Pioneer 21 Varieties. The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the research was carried out from August to November 2021. The location is located at an altitude of ± 50 m above sea level (masl), the soil type is the association of Latosol and Regosol, including type D rain (moderate). The experimental method used was an experimental method with a randomized complete block design (RCBD). The treatments given were a combination dose of compost, and plant spacing so that there were 12 treatment combinations where each treatment got 3 replications so that 36 experimental plots were obtained. The compost consisting of 3 levels, (K1: 10 tons / ha, K2: 15 tons / ha, and K3: 20 tons / ha), and the spacing of plants consisting of 4 levels, jajar legowo 2:1 ( 100 cm x 50 cm ) x 30 cm), jajar legowo 2:1 (100 cm x 40 cm ) x 30 cm), zig-zag (100 cm x 50 cm) x 30 cm), and zig-zag (100 cm x 40 cm) x 30 cm). The experimental results showed: (1) The combination treatment of compost fertilizer and spacing had significant effect on plant height at 28 DAP, 35 DAP and 42 DAP, stem diameter at 28 DAP, 35 DAP and 42 DAP, number of leaves at 35 and 42 DAP, area leaves at 28 DAP, and growth rate, ear length, ear diameter, dry shelled weight per plant and dry shelled weight per plot, (2) The highest dry shelled weight per plot was produced by a combination of treatment E, namely compost 15 tons/ha and plant spacing. jajar legowo 2:1 (100 x 50 x 30 cm) with a dry weight of 11.42 kg per plot (equivalent to 7.34 tons/ha), and (3) There was a significant correlation between plant height and number of leaves with dry shed weight. per plot at the age of 28 DAP, 35 DAP and 42 DAP in the medium category.